Use of Management Accounting Practices in Carbon Emission Management: Evidence from Australian Companies - Kumarasiri, Jayanthi (The journal of contemporary issues in business and government, 2015)
This study examines the use of management accounting practices by companies in managing carbon emission issues. The sample consists of 69 Australian companies that participated in the Carbon Disclosure Project (CDP) 2009 survey. Both qualitative and quantitative analyses of survey responses are conducted. In this investigation, relative absence of the use of accounting practices was uncovered. Given that the companies examined were large companies and the majority of them operated in carbon intensive or climate change exposed sectors, it is likely that this under-utilisation of accounting practices translates into a corresponding under-performance in carbon emission management. Acknowledgement: This paper is drawn from Kumarasiri’ s (2015) unpublished PhD thesis.